2011
DOI: 10.1093/brain/awq373
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and molecular genetic features of idiopathic infantile periodic alternating nystagmus

Abstract: Periodic alternating nystagmus consists of involuntary oscillations of the eyes with cyclical changes of nystagmus direction. It can occur during infancy (e.g. idiopathic infantile periodic alternating nystagmus) or later in life. Acquired forms are often associated with cerebellar dysfunction arising due to instability of the optokinetic-vestibular systems. Idiopathic infantile periodic alternating nystagmus can be familial or occur in isolation; however, very little is known about the clinical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 39 publications
4
65
0
1
Order By: Relevance
“…Consistently with this, we have observed the expression of FRMD7 within the developing horizontal neural integrator (nucleus prepositus and medial vestibular nuclei). 7,22 In this family, we report horizontal, vertical and torsional nystagmus associated with a PAX6 mutation. Neuroimaging in patients with PAX6 mutations have revealed abnormalities in the cerebellar grey matter.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Consistently with this, we have observed the expression of FRMD7 within the developing horizontal neural integrator (nucleus prepositus and medial vestibular nuclei). 7,22 In this family, we report horizontal, vertical and torsional nystagmus associated with a PAX6 mutation. Neuroimaging in patients with PAX6 mutations have revealed abnormalities in the cerebellar grey matter.…”
Section: Discussionmentioning
confidence: 81%
“…We have previously reported a phenotypic heterogeneity associated with nystagmus in families with FRMD7 mutations and also in patients with periodic alternating nystagmus. 7,22 These data suggest that the nystagmus phenotype is not defined solely by genotype.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…98 HCN/INS is characterized by periodic alternation of involuntary oscillations of the eye consisting of slow movement of the eye called slow phase followed by quick phase to focus on the object of interest called saccades. The pathophysiology of the disease is poorly understood.…”
Section: Human Congenital Nystagmus (Hcn)/infantile Nystagmus Syndrommentioning
confidence: 99%
“…Recently, it was shown that mutation of the FRMD7 gene on loci NYS1, which is expressed in neuronal tissue of the developing retina, mid brain, and hindbrain, is associated with INS. 98 INS has been modelled in zebrafish. 4,24 A large number of homozygous belladonna (bel) mutants were found to display a reversed OKR indicative of a projection defect.…”
Section: Human Congenital Nystagmus (Hcn)/infantile Nystagmus Syndrommentioning
confidence: 99%